Feasibility and safety of difficult laparoscopic cholecystectomy without using salvage procedures: a tertiary center experience - Kumari, Kona S. L.; Goud, G. Harishwar; Chowdhury, Sourav; Bhavsar, Ruchir M.; Shrivastava, Rishi R. (International Surgery Journal, 2025)
Background: Difficult laparoscopic cholecystectomy is associated with an increased risk of serious complications and a higher conversion rate. Iatrogenic injuries and conversion rates during laparoscopic cholecystectomy are still high which can be reduced with a surgeon’s experience, special techniques, and intraoperative investigations. The present study aims to determine the outcomes of performing laparoscopic total cholecystectomy rather than salvage procedures. Methods: A retrospective analysis of 100 patients who underwent difficult laparoscopic cholecystectomy between March 2023 and March 2024 was considered for this study. Inclusion criteria were abnormal anatomy, Mirizzi syndrome, Frozen Calot’s triangle, gangrenous gallbladder, and perforated gallbladder. Statistical analysis was done utilizing statistical package for the social sciences (SPSS) version 21.0, with a significance level of p<0.05 deemed significant. Results: Current results show that the mean age was 58 years (18-89 years) with male predominance (68%). Three major categories of difficulty were identified which include: difficult dissection of the Calot’s triangle in 42% of cases, difficulty in grasping and retracting the gallbladder (GB) in 45% of cases, and abnormal anatomy in 13% of cases. In 97% of patients, cholecystectomy was performed within the first 48 hours of admission. Among the total number of patients, 42% had phlegmonous, 12% had gangrenous cholecystitis and 5% had a subhepatic abscess. Total cholecystectomy was carried out in all patients without any damage control measures or conversion to open surgery and mortality was found to be 0%. Over a follow-up of 8 months, patients were performing well with no complications. Conclusions: Difficult laparoscopic cholecystectomy can be completed without conversion to open surgery or switch to salvage procedures. The utmost importance is to achieve a critical view of safety (CVS).